Manifest west: different roads: traversing the diverse roads of the West - Meridith, Larry K., editor; Western Press Books, publisher (Colorado State University. Libraries, 2014)
A literary anthology 2014.--From cover.
Different roads: traversing the diverse roads of the West
Keywords: West (U.S.) -- Literary collections